KAJIAN PEMILIHAN JENIS TUMBUHAN UNTUK RESTORASI HUTAN BERDASARKAN BEBERAPA PARAMETER FOTOSINTESIS - Ahmad, Tinia Leyli Shofia; Setiadi, Dede; Widyatmoko, Didik (Perhimpunan Biologi Indonesia, 2013)
Forest restoration is a process of ecosystem conditioning (soil, vegetation, and wildlife) in order to achieve similarpatterns and profiles to previous conditions and status before the ecosystem was disturbed, both in terms of speciescomposition and structure, and habitat functions. Restoration is a crucial part to maximize the conservation values ofbiodiversity and ecosystem functions. Eight different native plant species were assessed in this research while the photosyntheticparameters studied included the total chlorophyll content, carbohydrate content, CO2 sequestration capacity,leaf weight, leaf number, leaf area and leaf water content. Spectrophotometer was operated to analyse chlorophyllcontent, the Somogyi-Nelson method was used to calculate carbohydrate content, and leaf area was measuredusing the leaf area meter. The research results using the principal component analysis showed that each type of theplant species used for the restoration (2 years old after planting) had different characteristics in terms of photosyntheticparameters studied. Dacrycarpus imbricatus and Syzygium lineatum both had the highest carbohydrate contentsand the best abilities to absorb CO2. Sloanea sigun, Alstonia scholaris, Manglietia glauca, and Castanopsis argentea hadhigher total chlorophyll contents than others, while Altingia excelsa, M. glauca, A. scholaris, and Schima wallichii hadhigher water contents. A. scholaris, M. glauca, and S. sigun had heavier leaf weights. In contrast, M. glauca possessedthe widest leaves amongst the species observed.Keywords: forest restoration, photosynthetic parameters, native species